ANALISIS TINDAK TUTUR ILOKUSI PADA KUMPULAN CERPEN SENYUM KARYAMIN DAN IMPELEMENTASINYA SEBAGAI MEDIA PEMBELAJARAN DI SMP KELAS IX - Rika Kartika; Any Budiarti; Marlia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study discusses the problems encountered in the use of language and learning Indonesian. Indonesian is often used with many mistakes, especially in the world of education. Students often experience obstacles in understanding and using language properly and correctly. One of the language skills that students are less interested in is reading, due to the lack of awareness of the importance of reading in increasing knowledge. Another problem encountered in learning Indonesian is understanding the meaning of speech and the use of learning media. Understanding the meaning of utterances is often disturbed due to context and indirect disclosure. Meanwhile, the use of deep learning media is still lacking, especially in the use of technology. Many teachers experience obstacles in using learning media, so that student learning motivation becomes low. This study aims to understand the problems associated with language use and learning Indonesian. The results of this study are expected to provide useful insights and recommendations for educators and students in improving Indonesian language learning.